The Globalization of Science Curricula - Stacey, Oliver (IEA Research for Education, 2018)
Globalization; Science education; Science curricula; Large scale international assessments; Trends in International Mathematics and Science Survey; TIMSS; Policy borrowing; Curriculum reform; IEA Research for Education